Which temporal bone anatomical structures and pathologies could be best visualized by applying reconstruction to cross-sections obtained on an axial plane? - Esen Bostancı, Işıl; Düzgün, Fatih; Yılmaz Ovalı, Gülgün; Tarhan, Serdar; Pabuşçu, Yüksel (ENT Updates, 2017)
Objective: In this study, we aimed to identify the position in which temporal bone anatomical structures and pathologies could be best visualized by applying reconstruction to cross-sections obtained on an axial plane in temporal bone computed tomography (CT) scans. Methods: Sixty patients were examined with temporal bone CT between July 2008 and March 2009. We obtained multiplanar reformatted images by applying retro-reconstruction on various planes from the axial plane sections. Results: We determined that the reconstructed images increased the anatomical and pathological details and significantly contributed to evaluating the relationship between anatomical structures and their pathologies with other normal components. Conclusion: Obtaining multiplanar reformatted images by retro-reconstruction decreased the need for visualization of coronal sections used in standard temporal bone CT exams since the anatomical details were diversified using the new planes. In addition, the dose of radiation received by the patients and the duration of the examination could be reduced by eliminating routine coronal plane sections and obtaining new images using retro-reconstruction.